PENGARUH PERFORMA KEUANGAN, STRUKTUR PERUSAHAAN DAN KUALITAS AUDIT DALAM MANAJEMEN LABA - CYNTHIA YOLANDA; Ricardo Suhendra Wirjawan (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This research purpose is to test the influence of financial performance, company structure, and audit quality to earnings management. This research test whether the variables such as financial leverage, sales growth, company size, profitability, firm age, audit quality, auditor independence and managerial ownership have effect on earnings management. The object used in this research is non-financial companies that listed on Indonesia Stock Exchange (IDX) during the research period from 2018 to 2020. The samples are selected by using purposive sampling method and there are 106 companies that met the criteria. The data are analyzed using multiple regression. The result of this research shows that audit quality has effect on earnings management. The research also shows that other tested variables such financial leverage, sales growth, company size, profitability, firm age, auditor independence, and managerial ownership have no effect on earnings management.